Análisis de los peligros hidrometeorológico y caída de roca en la ciudad de Pucalá y CP Huaca Rajada y Sipán - Allende Ccahuana, Teófilo (2024)
The objective of the research is to develop an analysis of the hydrometeorological and rockfall hazards that impact the city of Pucalá and the populated centers of Huaca Rajada and Sipán, based on multi-criteria evaluation (MCE) techniques, where the variables of the susceptibility of the territory and the evaluation parameters for fluvial flooding, flooding, debris flow and rockfall hazards are identified. In addition, a matrix is used to assign weightings according to the relative importance of each variable and its descriptors with respect to the probability of increasing hazard levels. The variables and descriptors correspond to information obtained from sources of public and private entities and from field observations where the lithology, morphology and slope variables were validated as conditioning factors of the hazards, and with data from the Sipán station, maximum precipitation is obtained as a triggering factor. The hazard is related to a critical scenario for pluvial flooding (flooding) that presents maximum precipitation thresholds and affects the city of Pucalá, and another for fluvial flooding where there are sectors with exposure due to the overflowing of the Chancay River and irrigation canals. Meanwhile, the critical scenarios for rockfall and debris flow hazards occur in sectors where there are unstable conditions on the slopes of hills and mountains of Caballo Blanco hill and affect the local road that connects with other towns, and in sectors of alluvial-torrential material deposition where the town of Sipán is located.